2017
DOI: 10.1111/cpf.12433
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity interval training using whole‐body exercises: training recommendations and methodological overview

Abstract: HIIT whole body (HWB)-based exercise is a new calisthenics exercise programme approach that can be considered an effective and safe method to improve physical fitness and body composition. HWB is a method that can be applied to different populations and ages. The purpose of this study was to describe possible methodologies for performing physical training based on whole-body exercise in healthy subjects. The HWB sessions consist of a repeated stimulus based on high-intensity exercise that also include monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 36 publications
0
47
0
8
Order By: Relevance
“…An single acute bout high-intensity interval training based on whole body exercise was performed according to previoulslly publication of our group 17 in a session and involved 2 min warm-up followed by 20 sets of 30 seconds of all-out intensity at the participant's self-selected gearing and 30 seconds of passive recovery period between sets. The following exercises were used: jumping jack, mountain climb, burpee and squat jump.…”
Section: Methodsmentioning
confidence: 99%
“…An single acute bout high-intensity interval training based on whole body exercise was performed according to previoulslly publication of our group 17 in a session and involved 2 min warm-up followed by 20 sets of 30 seconds of all-out intensity at the participant's self-selected gearing and 30 seconds of passive recovery period between sets. The following exercises were used: jumping jack, mountain climb, burpee and squat jump.…”
Section: Methodsmentioning
confidence: 99%
“…Performing body-weight exercises in the home environment at a high intensity to mimic that of laboratory-based low-volume HIT may remove some of the barriers to exercise, including lack of time, a requirement for equipment, costs and difficulty with transport (Machado et al 2017). Only a handful of studies have investigated the efficacy of home-based exercise training programmes (Ong et al 2009;Halse et al 2014;Dadgostar et al 2016;Blackwell et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Gist et al 10 demonstrated that HIIT body work led to physiological development and was convenient with regard to time management, cost-effective, and required little operational management compared to traditional training methods. Although this modality is considered simple and easy to use, training load manipulation should be well monitored to guarantee feasible control, efficacy and security 11 .…”
Section: Introductionmentioning
confidence: 99%
“…These values can be obtained using the number of repetitions per overload used, distance covered, number of sprints and amplitudes reached. These values are all frequently used indicators 11 . The ITL can be considered an individual-specific physiological adaptation that has occurred as the result of a workload (physical training stress) provided by external ITL.…”
Section: Introductionmentioning
confidence: 99%